Ethnobotanical significance of Citrullus landraces and wild relatives in Sesheke, Kaoma, and Mumbwa Districts of Zambia - Silavwe, Chester; Chuba, David; Banda, Agripina; Kaimoyo, Evans; Maggs-Kolling, Gillian (Ethnobotany Research and Applications, 2025)
Background: Watermelon, cultivated globally, is an important genetic resource in traditional agricultural systems. Their ethnobotanical significance in such systems, however, remains underexplored, including within the Zambian context. This study explores the ethnobotanical significance of watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai, Cucurbitaceae) landraces, related species (C. amarus Schrad.) and their wild relatives in Sesheke, Kaoma, and Mumbwa Districts of Zambia. Methods: Utilizing a qualitative and quantitative approach through questionnaires and semi-structured interviews, data were collected and organized using Microsoft Excel and analyzed using the ethnobotanyR version 0.1.9 package in R version 4.4.2 (2024-10-31 ucrt) to calculate quantitative indices. Results: The study identified seven traditional cultivars: four C. amarus landraces (matanga, vikululu and sikululu), including kanyang’ombe, a wild form of C. amarus and three C. lanatus landraces (namunywa, mahapu, and makabe). Four categories of use were documented: food and nutrition, medicinal, fishing and fodder. Among these, the landrace sikululu in Sesheke recorded the highest ethnobotanical values (UR = 69, CI = 2.4, CVe = 0.9) within the Lozi-speaking community. Other landraces such as mahapu and kanyang’ombe were found to be more localized, likely influenced by cultural practices and environmental suitability, particularly in the semi-arid, sandy soil regions of Western Province. Conclusions: Landrace diversity and ethnobotanical values were highest in Sesheke and Kaoma compared to Mumbwa, reflecting both ecological and cultural influences. The observed differences in landrace characteristics and their uses underscore the importance of local knowledge in plant selection and conservation. These findings highlight the critical need for targeted conservation strategies to preserve both the genetic diversity and cultural relevance of traditional watermelon landraces in Zambia’s rural communities. Keywords: Citrullus amarus; C. lanatus; landraces; wild relatives; diversity; Ethnobotany; Ethnobotanical indices